Pelaksanaan Perjanjian Kredit Rumah Di PT. Bank BTN. Tbk Pekanbaru Oleh : Ferindoni 1209136087 (Perdata Bisnis) - Ferindoni '; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The embodiment of the people's welfare is characterized by increasing a decent life and dignity and insufficient basic needs are food, clothing, shelter, health, education, and employment. The house is a basic need and has a very important function for human life. To have a home, not all communities can purchase for cash, especially low income community group and the medium. Housing loan program is implemented by the bank that has the function or main activity is collecting funds from the public and channel them back to the community. State Savings Bank is one of the state banks designated to implement the program of housing loans with a credit facility, called the Home Loan Savings Bank or often known as KPR-BTN as a program in the field of public housing. The author chose PT. Bank BTN. Tbk. Pekanbaru as the object of the study site because in my experience relating to the title, as well as PT. Bank BTN. Tbk is a bank that has become the Financing of home loans in Pekanbaru. PT. Bank BTN.Tbk Pekanbaru, the authors conducted a study giving home loans with an interest rate of 7.25% (fixed rate) in 2014, and 5% interest (fixed rate) in 2015.Issues examined in this study are: First, How the home loan agreement implementation in PT. Bank BTN. Tbk Pekanbaru? Second, Any defaults that occurred in the implementation of the home loan agreement in PT. Bank BTN. Tbk Pekanbaru, Third How barriers and efforts made by PT. Bank BTN. Tbk Pekanbaru in the completion of tort committed by the debtor in the implementation of home loans?This type of research is a sociological law research. Source data used are primary data and secondary data, engineering data collection using interviews and literature study. In this study the authors used a qualitative analysis, in drawing conclusions using inductive method of thinking.Results from this study is the first, full implementation of the processes of granting credit, debtor must meet dengen housing developers who want to buy, then define housing units, and determining the Bank that will be used as a creditor. After that the debtor meets the requirements to be submitted to the bank. Second, tort either of the banks as creditor or of the debtor such as slow granting a certificate at the letter in full, bad credit and Sell / Rent Object without the knowledge of bank credit. third, Barriers In Settlement Default The dilakukukan By Debtor In Execution Mortgage Debtors are no longer able to pay, the Borrower No Good faith, Developer Obscure Object of credit in case of dispute.Keywords: Agreement - Mortgage - PT. Bank BTN. Tbk